Responding to (un)reasonable requests by an authority - Vittorio Pelligra; Tommaso Reggiani; Daniel John Zizzo (Cardiff University, Cardiff Business School, 2020)
We consider the notions of static and dynamic reasonableness of requests by an authority in a trust game experiment. The authority, modelled as the experimenter, systematically varies the experimental norm of what is expected from trustees to return to trustors, both in terms of the level of each request and in terms of the sequence of the requests. Static reasonableness matters in a self-biased way, in the sense that low requests justify returning less, but high requests tend to be ignored. Dynamic reasonableness also matters, in the sense that, if requests keep increasing, trustees return less compared to the same requests presented in random or decreasing order. Requests never systematically increase trustworthiness but may decrease it.
Keywords: C91; D01; D03; D63; 330; trust; trustworthiness; authority; reasonableness; moral wiggle room; moral licensing